2010
DOI: 10.1089/jwh.2008.1028
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality Trend in South East Nigeria: Less Than a Decade to the Millennium Developmental Goals

Abstract: The MMR is worsening. If this trend is not reversed, Nigeria may not be able to achieve the millennium developmental goal number 5 (MDG 5). A prospective, multicenter, community-based study is needed to fully assess the magnitude of the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
(12 reference statements)
3
26
1
Order By: Relevance
“…This is similar to the report by Nwagha et al,5 but slightly differs from reports by Mairiga et al4 and Agan et al7 who found sepsis to be less prominent. Many of the cases handled by the obstetricians at the study center are cases referred from private hospitals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to the report by Nwagha et al,5 but slightly differs from reports by Mairiga et al4 and Agan et al7 who found sepsis to be less prominent. Many of the cases handled by the obstetricians at the study center are cases referred from private hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown the relatively high maternal mortality rate in Nigeria 27. Maternal deaths have remained high despite many efforts in reducing it 5. A more concerted effort is needed in the implementation of already existing policies on reduction of maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The MMR of 1098 per 100 000 live births at NAUTH between 2004 and 2010 is very high but similar to that reported in other hospitalbased studies in Nigeria [12,13]. This ratio is less than the 2849 per 100 000 and 2151 per 100 000 deliveries reported in hospitalbased studies conducted in the Nigerian states of Gombe [14] and Sokoto [15], respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, economic, geographical, sociocultural, and patient demographic peculiarities were not considered. Consequently, maternal mortality and morbidity has remained embarrassingly high, [31] and the attainment of the Millennium Development Goals is in doubt. Unfortunately, there is a dearth of information on the relationship between some micronutrients (Cu and Zn) status, parity, and obesity indices in pregnant and nonpregnant women.…”
Section: Introductionmentioning
confidence: 99%